2019
DOI: 10.1002/celc.201900340
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Edge‐Site‐Enriched α‐Co0.9Fe0.1(OH)x Nanoplates for Efficient Overall Water Splitting

Abstract: Developing efficient electrocatalysts from the earth-abundant transition-metal family is a great challenge for overall water splitting. Herein, we developed an approach to regulate the morphology and electronic structure of α-Co 0.9 Fe 0.1 (OH) x nanoplates, in which FeCl 2 (as a precursor) plays a significant role under reflux conditions. The resulting 2D α-Co 0.9 Fe 0.1 (OH) x nanoplates exhibit more accessible edge active sites and more high-valence Co species to boost its intrinsic activity. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…In Fe-doped materials, the Co 2p spectrum can also be bifurcated into spin–orbit doublets and two satellite peaks (Figure a). The first doublet was observed at 780.2 and 795.9 eV for Co 3+ , and the second doublet was observed at 781.7 and 797.2 eV for Co 2+ corresponding to Co 2p 3/2 and Co 2p 1/2 , respectively (Figure a) . The spin–orbit splitting values of the Co 2p 3/2 and Co 2p 1/2 were more than 15 eV, which supports the presence of both Co 3+ and Co 2+ in Fe-doped materials .…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…In Fe-doped materials, the Co 2p spectrum can also be bifurcated into spin–orbit doublets and two satellite peaks (Figure a). The first doublet was observed at 780.2 and 795.9 eV for Co 3+ , and the second doublet was observed at 781.7 and 797.2 eV for Co 2+ corresponding to Co 2p 3/2 and Co 2p 1/2 , respectively (Figure a) . The spin–orbit splitting values of the Co 2p 3/2 and Co 2p 1/2 were more than 15 eV, which supports the presence of both Co 3+ and Co 2+ in Fe-doped materials .…”
Section: Resultssupporting
confidence: 51%
“…In CoFe-nanomesh materials, the Co 2+ /Co 3+ ratio decreased with increased Fe-doping (Table S3, SI) since the presence of Fe­(NO 3 ) 3 in the solution decreases the pH, which presumably can oxidize more Co 2+ to Co 3+ (Table S3, SI) . For all Fe-doped Co­(OH) x , Fe 2p XPS showed peaks at 711.8 and 724.2 eV, which can be attributed to Fe 3+ 2p 3/2 and Fe 3+ 2p 1/2 , respectively (Figure b) . The peak at 715.2 eV was associated with the iron surface peak and also indicated that the iron was present in more than one coordination environment (Figure b) .…”
Section: Resultsmentioning
confidence: 98%
“…These indicate the strong electronic interaction between Cu and Fe with α-Co(OH) 2 . 57 The high-resolution Cu XPS curve of Cu-Co(OH) 2 can be ascribed as Cu 2p 3/2 (935.2 eV) and Cu 2p 1/2 (955.1 eV) with two shake satellite peaks (943.1 and 962.9 eV). For the high-resolution Fe XPS spectra of Fe-Co(OH) 2 , two main peaks of Fe 2p 3/2 (712.6 eV) and Fe 2p 1/2 (725.8 eV) with the satellite peak at 717.6 eV are observed, demonstrating the presence of Fe 3+ .…”
Section: Results and Discussionmentioning
confidence: 96%
“…For the high-resolution Fe XPS spectra of Fe-Co(OH) 2 , two main peaks of Fe 2p 3/2 (712.6 eV) and Fe 2p 1/2 (725.8 eV) with the satellite peak at 717.6 eV are observed, demonstrating the presence of Fe 3+ . 57 Fe 3+ is usually considered as a redox-active species that can cooperate with Co to participate in the redox-hopping-type charge transfer, resulting in better OER activity. 26…”
Section: Results and Discussionmentioning
confidence: 99%
“…The slope is between 30 and 50 mV dec -1 for all samples, consistent with reports on materials with similar compositions. 45,49,5045,49,50 The slope gradually shifts to lower values with increased Fe-content in the formamide series, but a much more abrupt change occurs in the water series (Figure 4D).…”
Section: Resultsmentioning
confidence: 98%